Working Capital Management Impacts on Consumer Cyclical Retail Firm’s Financial Performance - Triwardhanie, Nindya Kartika; Virdausy, Siti Mariah; Mardiyani, Mardiyani; Maiyaliza, Maiyaliza (Journal Research of Social Science, Economics, and Management, 2026)
As the world has faced many economic crises and periods of instability, an appropriate strategy is needed to maintain sustainability and enhance the resilience of firms. The purpose of this study is to determine the impact of working capital management on the financial performance of consumer cyclical retail firms listed on the Indonesia Stock Exchange during the 2021–2024 period, with firm size as a moderating variable. As a quantitative study with a causal-associative approach, this research employed the Moderated Regression Analysis model using panel data. The samples used in this study were derived from secondary data through purposive sampling, resulting in 52 data observations. The results show that WCM practices, as measured by CCC, have a significant negative influence on ROA. In addition, WCM policies measured by WCIP have a significant positive influence on ROA, while WCFP has a significant negative influence on ROA. This study also found that firm size has a significant moderating effect on both the CCC–ROA relationship and the WCFP–ROA relationship. Thus, this study recommends the optimalization of WCM practices in day-to-day operations by improving the efficiency of its components. It is also recommended to adopt a conservative investment policy approach to ensure operational stability. On the other hand, large firms are advised to adopt an aggressive financing policy, while small firms should adopt a conservative approach to maximize profitability.